Constructed wetland systems: low cost treatment for sanitary sewage in rural areas (Research, Society and Development, 2020)
In Brazil, there is a high need for sewage collection and treatment, which is why it is necessary to adopt efficient and low-cost technologies that promote basic sanitation in the municipalities. One of these technologies is the Constructed Wetlands System (CW, which promotes sewage treatment before launching into water courses. This study evaluated the performance of CW system, which tested the association of two plant species, Hedychium coronarium (Garland-lily) and Typha domingensis (Southern cattail). The system was implemented in the district of Brejaúba, belonging to the municipality of Conceição do Mato Dentro - MG.  Samples were collected at three points in the system and submitted to analysis of the Biochemical Oxygen Demand (BOD), total solids, sediment solids, pH, turbidity and total nitrogen. Average reductions of 83% in BOD, 85% in total solids, 49.6% in nitrogen concentration, 99.9% in sediment solids and 89.7% in turbidity were observed. According to current legislation, the system effluent can be poured into the water course. Thus, analysis of the results detected a reduction in all parameters evaluated, demonstrating that the CW is an extremely promising system, since it is an efficient, low-cost system and contributes to the quality of water courses.